POLITENESS STRATEGIES USED BY STAN SMITH IN AMERICAN DAD SITCOM, SEASON 1 (STAN OF ARABIA) - DELICIA, VANIA (Jurnal Ilmiah Mahasiswa FIB, 2014)
This study is about politeness strategies in American Dad Sitcom, Season 1 (Stan of Arabia) which reflects the use of politeness strategies by an American (StanSmith) who to adapts on Saudi Arabia which has different culture.There are 2 problems to be solved; (1.a) What are FTA performed by StanSmith on American Dad sitcom, Season 1 (Stan of Arabia), (1.b) What are types ofPoliteness Strategies performed by Stan Smith character on American Dad sitcom,Stan of Arabia and (2) what are the factors causing the strategies to appear.This study used qualitative approach to analyze the data by analyzing documentand interpreting the utterances. The data are taken from the dialogs in the moviescript.The result of this analysis shows that Stan Smith did the FTAs for 32 times; 16acts threatening positive face and 16 ones threatening negative face. 23 of them arerealized in bald on record strategy and 9 utterances are performed with politenessstrategies. The 16 threatening positive face are expression of ridicule, complain andinsult, bringing bad or good news to the addressee, apology, disapproval, irreverence,expression of violence. The 16 threatening negative face are warning, order andrequest, reminding, excuses.  Stan Smith also applied two kinds of politenessstrategies in his sentences: 7 utterances using positive politeness strategies and 2utterances using negative politeness strategies. The 7 positive politeness strategies arestrategy 8 (jokes), strategy 12 (include both S and H in the activity), strategy 3(intensify interest on H), strategy 11(being optimistic). The 2  negative politenessstrategies that performed by Stan Smith character is strategy 5(give deference).It can be concluded that Stan applies FTA bald on record frequently thanminimizing the risk of damaging addressee’s face because his desire of beingfreedom as a man in male-dominated society and be respected by others wasthreatened. Writer hopes the reader search more object and theories which reflectedthe appliance of FTA and politeness in the daily life.Keywords: Politeness Strategies, Face Threatening Acts (FTAs)